PEMETAAN KABUPATEN KOTA DI PROVINSI JAWA TIMUR BERDASARKAN TINGKAT KASUS PENYAKIT MENGGUNAKAN PENDEKATAN AGGLOMERATIF HIERARCHICAL CLUSTERING - Amin Septianingsih (LPPM Universitas Bina Bangsa, 2022)
Health is a human right that is one of the indicators of welfare that must felt by all people following the ideals of the Indonesian people to realize a high degree of health. The high level of public health is one of the base capital for realization of the implementation of national development. One indicator of policy target evaluation in the health sector is the availability of adequate public health facilities and services. In addition, the level of the number of people suffering from disease complaints needs to be the attention of the government and the community to become the material for evaluating policy targets in the health sector. Based on data on the percentage of the population who have health complaints in 2020 obtained from the BPS of the Republic of Indonesia, East Java Province is ranked 7th, which is 32.8%. While the data in 2021 East Java Province is ranked 8th at 28.55%. This figure is quite high compared to other provinces so the East Java Provincial government needs to pay attention to reducing cases of disease complaints. Therefore, this study aims to analyze and map regencies and cities in East Java Province based on the distribution of the characteristics of the number of disease cases in each regency and city using the Agglomerative Hierarchical Clustering method. Based on the value of the cophenetic correlation coefficient, the average linkage method is the best method with the optimal number of clusters formed 4 clusters based on the cluster validation test using the connectivity validity index test, Dunn index, and silhouette. The results of this study can be used as a reference for the government of East Java Province in taking policies to improve national development planning in the health sector to increase the high level of public health